Biologická úloha mikroRNA v živočišných buňkách - Mráz, Marek (2006)
MicroRNAs (miRNA) are small non-coding RNAs that negatively regulate gene expression in a sequence-specific manner. Post-transcriptional silencing of target genes by miRNA occurs either by specific cleavage of homologous mRNA or by specific inhibition of protein synthesis. MicroRNAs were first discovered in Caenorhabditis elegans as genes required for regulation of developmental timing. MiRNAs are essential regulators of various processes such as proliferation, differentiation, development, cell death and interaction between virus and host cell. Several human diseases including cancer are associated with aberant regulation of miRNAs expression or deficiency in miRNA biogenesis.In this work I review both the biogenesis and functions of microRNAs in animal cells and also focus on possible relations between microRNAs and human disease, mainly cancer.